Postpartum Infection can be a Disaster - Shama Chaudhry; Rubina Hussain (ziauddin University, 2024)
Abstract: Endometritis is the most common infection that occurs postpartum. Postpartum endometritis is tenfold to 20-fold more common among women who delivered by cesarean section than women who delivered vaginally. It can present with puerperal pyrexia, abscess formation & rarely rupture of uterus. Reported risk factors for dehiscence of the lower segment uterine scar following CS are multiparty, infection, and an incision placed too low in the lower uterine segment. The case presents a report of a 34 year old female Para 3+0 who was presented in emergency with high grade fever and abdominal pain. She undergone a caesarean delivery 9 days prior to presentation in a private clinic. Due to infection her uterus was found to be ruptured on exploratory laparotomy which is reported very rarely. Uterus was irreparable so obstetrical hysterectomy was done &patient was kept in ICU. Key Words: Endometritis, Obstetrical Hysterectomy, Chorioamnionitis.